Fiscal Federalism and European Health System Decentralization: A Perspective - Joan Costa-i-Font (London School of Economics and Political Science (LSE), European Institute, 2012)
How does fiscal decentralisation affect the development of a health system?Evidence from health care decentralisation in Europe can offer some insights to the question above. This paper addresses the effects of health care decentralisation in Europe, and reviews some of the key questions on the design of a health system. We argue that contrary to old mobility argument, the effects of health care decentralisation result from tighter political agency, which generally stands as an alternative to health care privatisation. However, whether efficiency improves after a process of decentralisation depends heavily on the incentives fiscal design exerts on cost –containment, inter-jurisdictional competition, policy innovation and diffusion. Experiences of health care decentralisation highlight important concerns associated with vertical imbalances and limited horizontal imbalances. Finally, health care decentralisation can give rise to a new regional political cycle where citizens can reward or penalise the performance of health policy.
Keywords: H51; I18; 330; health systems decentralisation; fiscal federalism; health care; political agency